An integrated sea-land approach for mapping geomorphological and sedimentological features in an urban microtidal wave-dominated beach: a case study from S Sardinia, western Mediterranean. Issue 2 (30th November 2017) - De Muro, Sandro; Ibba, Angelo; Simeone, Simone; Buosi, Carla; Brambilla, Walter
ABSTRACT: An integrated cartographic approach has been used to summarize different data (geomorphological, sedimentological, hydrodynamic, ecological and anthropic) from an urban microtidal, wave-dominated beach and adjacent inner shelf in a comprehensive and easily readable mapping output. The study area is located in S Sardinia (Italy, Mediterranean Sea) and focuses on Poetto beach. All the data in this study were processed to produce a Main Map (1:6400 scale) showing the key characteristics of the entire area and three detailed secondary maps (1:56, 000 and 1:59, 000 scale) that include topographic and eco-graphic profiles, the distribution of sedimentary facies and the main anthropic impact. This map, providing detailed information on the beach dynamics, human impact and the marine ecological status of the Poetto urban beach, represents a useful new tool to facilitate environmental conservation and beach management.